2023
DOI: 10.1111/gcb.17029
|View full text |Cite
|
Sign up to set email alerts
|

Spatial asynchrony and cross‐scale climate interactions in populations of a coldwater stream fish

George P. Valentine,
Xinyi Lu,
Evan S. Childress
et al.

Abstract: Climate change affects populations over broad geographic ranges due to spatially autocorrelated abiotic conditions known as the Moran effect. However, populations do not always respond to broad‐scale environmental changes synchronously across a landscape. We combined multiple datasets for a retrospective analysis of time‐series count data (5–28 annual samples per segment) at 144 stream segments dispersed over nearly 1,000 linear kilometers of range to characterize the population structure and scale of spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 189 publications
(225 reference statements)
0
4
0
Order By: Relevance
“…Valentine et al. (2023) also observed more spatial synchrony for juvenile brook trout than adults across the southern Appalachian region, and they attributed this to regional climate trends that affect fish abundance. Likewise, Kanno et al.…”
Section: Discussionmentioning
confidence: 98%
“…Valentine et al. (2023) also observed more spatial synchrony for juvenile brook trout than adults across the southern Appalachian region, and they attributed this to regional climate trends that affect fish abundance. Likewise, Kanno et al.…”
Section: Discussionmentioning
confidence: 98%
“…Prolonged high summer temperatures can cause physiological stress and adversely affect spawning (Warren et al., 2012; Xu et al., 2010), and high flows during winter and spring can result in bed scouring events that cause high mortality in young‐of‐the‐year (YOY) (Kanno et al., 2015; Roghair et al., 2002). However, there is limited knowledge on how differently trout populations respond to seasonal weather patterns along the environmental gradient across their native range (Valentine et al., 2024).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the naturally fragmented habitats occupied by brook trout could be instrumental in generating microgeographic variation (Wood et al, 2014) and stabilizing dynamics over larger scales, thereby buffering the species against disturbance . While brook trout population dynamics are likely to be more synchronized in southern range margins with warmer climates, recent studies in these regions nonetheless have shown evidence of demographic variation and subtle differences within and among streams (Andrew et al, 2022;Kanno et al, 2016;Valentine et al, 2024), which can covary with watershed geology (Hartman et al, 2007) and elevation (Kanno et al, 2015). Thus, fine-scale portfolio effects could potentially alleviate regional climate-induced extinction risk throughout much of the species range.…”
Section: Portfolio Effectsmentioning
confidence: 99%
“…Similarly, only 11 Cape Race populations had sufficient data for this study, which limited the scope of inference when assessing drivers of population variation. Future studies of brook trout could gain more robust insight into the prevalence, causes, and consequences of asynchrony by analyzing more populations with longer time series across a larger portion of their native range, as done in recent studies of salmonids (e.g., Donadi et al, 2023;Valentine et al 2024). Second, the results of this study were based on observations of brook trout age-1 and older, but ignored age-0 (young-of-the-year) individuals that were often too small to be comprehensively sampled by electrofishing (Dolan & Miranda, 2003).…”
Section: Limitationsmentioning
confidence: 99%